The Influence Of Different Aeration Systems On Growth Performance Catfish (Clarias sp.) - AlBaihaqi, Lalu Wirahadi; Marzuki, Muhammad; Setyono, Bagus Dwi Hari (Program Studi Budidaya Perairan Universitas Mataram, 2024)
Catfish is a freshwater consumption fish that is most widely cultivated in Indonesia, occupying the top position in total production, catfish has contributed more than 10% of the national aquaculture production with a growth rate of 17 to 18%. Catfish has a fairly high protein content and is very competent to improve human nutrition, because it is classified as a high quality food and its uniqueness is a must. Due to the high density of cultivation, a technology is needed that supports the maintenance of oxygen content, namely microbubble. This research was conducted for 50 days by observing the growth of catfish in 3 different conditions, namely without aerator, with conventional aerator and microbubble. The results showed that the absolute weight and absolute length without aeration were 5.2 g and 3.5 cm. then with a conventional aerator it produces 5.3 g and 3.5 cm. and on Microbubble it is 9.2 g and 7.2 cm. Judging from some of the parameter test results, it shows that raising catfish using microbubble increases the growth rate and productivity of catfish.